The Effect Of Health Education Through Animated Videos On The Level Of Anxiety Of Adolescent Females Experiencing Dysmenorea At Smpn 6 Maja Year 2026 - Agriyaningsih Oktaviana Hadi; Ade Anwar; Lina Mardianti; Siti Nurholijah (Jurnal Ners, 2026)
Dysmenorrhea is a reproductive health issue frequently experienced by adolescent girls that can cause anxiety, thereby interfering with daily activities. Objective : To analyze the effect of health education via animated video on the anxiety levels of adolescent girls experiencing dysmenorrhea at SMPN 6 Maja in 2026. Methods : This study employed a quantitative method with a quasi-experimental design, specifically a one-group pretest-posttest design. The study population consisted of 67 female adolescents experiencing dysmenorrhea at SMPN 6 Maja. A total sampling technique was used, meaning the entire population served as the study respondents. Anxiety levels were measured using the Hamilton Rating Scale for Anxiety (HARS) questionnaire. Data analysis was conducted using univariate and bivariate methods. A normality test using the Kolmogorov-Smirnov test indicated that the data were not normally distributed (p<0.05); Therefore, the Wilcoxon Signed-Rank Test was used for the bivariate analysis, with ethics number KEPK/UMP/290/V/2026 Results : Research Results: Prior to the health education intervention using animated videos, the majority of respondents experienced very severe anxiety (n=64; 95.5%), while three respondents (4.5%) experienced severe anxiety. Following the intervention, anxiety levels decreased, with 58 respondents (86.6%) falling into the moderate anxiety category and nine respondents (13.4%) into the mild category. The Wilcoxon Signed-Rank Test yielded an Asymp. Sig. (2-tailed) value of 0.000 (p<0.05), indicating a significant effect of health education via animated videos on the anxiety levels of adolescent girls experiencing dysmenorrhea. Conclusion : Health education using animated videos has a significant effect on reducing anxiety levels among adolescent girls experiencing dysmenorrhea at SMPN 6 Maja in 2026. Animated video media can serve as an effective alternative for reproductive health education for adolescent girls.